Effect of prehospital transportation on 24-h fluid volume, a post hoc analysis of a multicenter, prospective, observational study on fluid volumes in patients with suspected infection - Jensen, Marie Egebjerg; Kølsen-Petersen, Jens Aage; Kirkegaard, Hans; Jessen, Marie Kristine (Frontiers in Medicine, 2022)
Introduction: Sepsis is a leading cause of death and fluid administration is part of the treatment. The optimal fluid therapy remains controversial. If the patient is transported by emergency medical services (EMS), fluids can be initiated during transportation, which may result in increased overall fluid administration and fluid overload, which may be harmful. The aim of the study was to investigate the effect of EMS transportation on 24-hour fluid administration in patients with suspected infection. Methods: This is a post-hoc analysis of a prospective, multicenter, observational study, conducted in three Danish Emergency Departments (EDs), January 20-March 2, 2020, aiming at describing fluid administration in patients with suspected infection. Patients were stratified into the groups: simple infection or sepsis, in accordance with SEPSIS-3-guidelines. The primary outcome of the current study was 24-hours total fluid volume (oral and intravenous) stratified by transportation mode to the EDs. Main results: Total 24-hour fluids were registered for 734 patients. Patients with simple infection or sepsis arriving by EMS (n=388, 54%) received mean 3774 ml (standard deviation (SD): 1900) and non-EMS received 3627 ml (SD: 1568); mean difference (MD) was 303 ml [95% Cl: 32; 573] adjusted for age, site, and total SOFA-score. Patients brought in by EMS received more intravenous fluids (MD: 621 ml [95% Cl: 378; 864]) and less oral fluids (MD: -474 ml [95% CI: -616; -333] than non-EMS patients. Conclusion: Patients transported by EMS received more intravenous fluids and less oral fluids but overall, more fluid in total in the first 24-hours than non-EMS after adjusting for age, site and SOFA-score.